2019
DOI: 10.1007/s40200-019-00407-0
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the effectiveness of foot care education in rural clinics

Abstract: Purpose Approximately 13.3% of Mississippi's adult population lives with diabetes, with a higher prevalence among racial, ethnic, and socioeconomic minorities. However, there is no recorded data regarding the effectiveness of education on foot ulcer prevention provided to patients in the rural clinic network. Future studies to evaluate the effectiveness of foot care education would benefit from a racially-, ethically-, and socioeconomically-diverse education program. Methods This study combined verbal and visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…After assessing the knowledge the post testvalue is out of 50 samples 35(70%) had Adequate knowledge, 15(30%) had inadequate knowledge and0 (0%) had poor knowledge. The findings of the study conducted by the author Gloria Green-Morris [11], An evaluation of the effectiveness of providing foot care education in a rural clinic setting, supports this study. The result of the study show that after educating the diabetic clients about the diabetic foot care, 100% of participants of participants agreed that checking their foot ulcer are caused by taking care of their feet.77.8% believes that checking their feet decreased the likelihood of foot ulcer formation and all the participants had the ability to choose shoes that properly feet their feet.…”
Section: Discussionsupporting
confidence: 70%
“…After assessing the knowledge the post testvalue is out of 50 samples 35(70%) had Adequate knowledge, 15(30%) had inadequate knowledge and0 (0%) had poor knowledge. The findings of the study conducted by the author Gloria Green-Morris [11], An evaluation of the effectiveness of providing foot care education in a rural clinic setting, supports this study. The result of the study show that after educating the diabetic clients about the diabetic foot care, 100% of participants of participants agreed that checking their foot ulcer are caused by taking care of their feet.77.8% believes that checking their feet decreased the likelihood of foot ulcer formation and all the participants had the ability to choose shoes that properly feet their feet.…”
Section: Discussionsupporting
confidence: 70%
“…The guidelines emphasize variables that can negatively affect foot health in addition to providing appropriate self-care strategies that support and sustain foot health. This all-encompassing strategy seeks to assist people in identifying and reducing hazards, maintaining long-term foot health, and averting further issues [57].…”
Section: Patient-centered Care and Education Diabetes-related Wound P...mentioning
confidence: 99%
“…Yet, older adults often face internal (e.g., physical ability, perceived importance, education level and knowledge) and external (e.g., communication between patient-provider, seasonal changes, finance) barriers to seeking and/or receiving footcare, and these underpin poorer health outcomes [7,8]. Findings from a recent qualitative study identified that older adults benefitted from advice, education, and support to maintain appropriate footcare, yet evidence of the effectiveness of interventions are lacking [9], and there are many challenges to delivering preventative footcare interventions [10]. Effective health promotion strategies are fundamental to enhancing footcare and promoting interventions which target the factors influencing health behaviors.…”
Section: Introductionmentioning
confidence: 99%